EXISTENCY ROLE OF THE GENERAL ELECTION SUPERVISORY AGENCY IN LAMPUNG LAW ENFORCEMENT OF THE 2019 ELECTION - Maimun Maimun; Rudi Santoso (Law Faculty of Universitas Bandar Lampung, 2021)
The Lampung election supervisory body has performed its role effectively byprocessing these findings and reports. Although, in the process, only one criminal case reached a trial and was decided by the Court. The Lampung general election supervisory body has a number of obstacles faced in prosecuting 2019 Election violations. These include the inadequate role of the Integrated Law Enforcement Center (Gakkumdu). This is due to differences in backgrounds and good views between the General Election Supervisory Agency, the Police and the Attorney General's Office in observing cases of election violations. Another factor is Human Resources. Human resources owned by the General Election Supervisory Agency are still very few, coupled with the number of budgets and inadequate facilities. In the process, only one criminal case has reached trial and is decided by the Court. The Lampung general election supervisory agency has a number of obstacles faced in prosecuting 2019 Election violations. These include the inadequate role of theIntegrated Law Enforcement Center (Gakkumdu). This is due to differences inbackgrounds and good views between the General Election Supervisory Agency, the Police and the Attorney General's Office in observing cases of election violations. Another factor is Human Resources. Human resources owned by the General Election Supervisory Agency are still very few, coupled with the number of budgets and inadequate facilities. In the process, only one criminal case has reached a trial and is decided by the Court. The Lampung general election supervisory agency has a number of obstacles faced in prosecuting 2019 Election violations. These include the inadequate role of the Integrated Law Enforcement Center (Gakkumdu).